Phenotypic and Molecular Detection of Extended-spectrum beta-lactamase among Ceftazidime Resistant Pseudomonas aeruginosa Isolated from Wound Swab. - Sultana, Sharmin; Paul, Shikha; Naher, Akhtarun; Akter, Rahima; Khan, Tarina (Bangladesh Journal of Medical Microbiology, 2018)
ESBL producing Pseudomonas aeruginosa has been reported to be an important cause of nosocomial infection. The study was undertaken to determine ESBL producing Pseudomonas aeruginosa by phenotypic method and to detect bla OXA-10 ESBL gene by molecular method. A total of 288 wound infection cases attending the in-patient department of Mitford Hospital and Dhaka Medical College Hospital were enrolled for this study. Pseudomonas aeruginosa was isolated following standard procedure and subjected to antimicrobial susceptibility test by disc-diffusion method. Ceftazidime resistant strains were confirmed by MIC by agar dilution method. Confirmed ceftazidime resistant strains were tested for ESBL production by CLSI phenotypic confirmatory disc diffusion test (PCDDT) and bla OXA-10 ESBL gene was identified by employing conventional PCR. Out of 92 Pseudomonas aeruginosa, confirmed ceftazidime resistant strains were 60. PCDDT detected 49 (81.67%) ESBL producers and PCR detected 44 (73.33%) positive strains for bla OXA-10 ESBL gene among 60 ceftazidime resistant strains of Pseudomonas aeruginosa. The study showed high proportion of ESBL producers among ceftazidime resistant Pseudomonas aeruginosa. Bangladesh J Med Microbiol 2018; 12 (1): 15-19